O Processo de Certificação de Hortaliças na Cooperativa Sul Ecológica de Agricultores Familiares Ltda.: um estudo de caso. - Andersson, Fabiana da Silva (2011)
This dissertation examines the process of certification with social control for direct sale, initiated with the ecological family farmers who are integrated into the Cooperativa Sul Ecológica de Agricultores Familiares Ltda (South Ecological Cooperative of Family Farmers Ltd) coming from the cities of Pelotas and São Lourenço do Sul, in the state of Rio Grande do Sul, Brazil.The choice for these two cities has been due to the existence of a permanent institutional market over the last years. This enabled the effective production of vegetables by the farmers of ecological base inserted in each municipality, aiming at serving the Food Acquisition Program (PAA) and the National School Feeding Programme (PANE). These programmes prefer organic foods, reason why, from 2001 on, the latter must present organic quality assurance through certification. The South Ecological Cooperative deals with the organic issue taking into account more than the techno-economic determinants, incorporating principles of agroecology for the production of vegetables. To this end, the certification with social control for direct selling is the one that best meets the current needs of the Cooperative. In order to qualify the techniques established by the State, it is indispensable to characterize the family farmers of ecological base integrated into the South Ecological Cooperative, know their means of production and identify their chances of representation in the perspective of organic production norms and the institutional market. Through interviews with a semi-structured questionnaire and participant observation, the research with 30 families belonging to the Cooperative and active in the institutional market made it possible to collect answers for the questions previously formulated. The data obtained from research clearly demonstrate the importance of a legislation based on the daily routines of rural subjects. Additionally, these data highlight the knowledge gained through practices in group by the investigated farmers on the techniques used in the ecological basis production of vegetables, meeting the required standards for organic production. It is also remarkable these subjects' constant participation in the events of their surroundings as well as in other environments so as to enhance social control and thus ensure the organic quality of the foods intended for the feeding of nearby societies. Consequently, the possibility of exchanging experiences among members of the institutional market is favored.